Age, Parity, Physical Activity, Birth Weight, and the Risk of Perineum Rupture at PKU Hospital in Delanggu, Klaten, Central Java - Hastuti, Tri Ari; Mudigdo, Ambar; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2016)
Background: Physiologic vaginal delivery of offspring may cause spontaneous unintended perineum tear (rupture) with varying degrees. Perineum rupture is the second leading cause of post-partum bleeding after uterine atony. The purpose of this study is to analyze the relationship between age, parity, physical activity, birth weight, and the risk of perineum rupture.Subject and Methods: This was an analytic observational study with cross sectional design. This study was carried out at PKU Hospital, Delanggu, Klaten, Central Java. A total of 78 mothers giving birth at the maternity ward were selected for this study stratified random sampling. The independent variables were age, parity, physical activity, and birth weight. The dependent variable was perineum rupture. The data were collected by interview and observation, and then analyzed using path analysis model.Results: Maternal age Ã¢â°Â¥ 35 years old (b = 3.36; 95%CI = 0.91 to 5.80; p = 0.007) increased the risk of perineum rupture, and it was statistically significant. Sufficient physical activity (b =-3.16; 95% CI =-5.05-1.27 ; p = 0.001) and multiparity (b =-4.05; 95% CI =-6.62 to -1.50; p = 0.002) decreased the risk of perineum rupture, and it was statistically significant. Birth weight did not show significant effect on the risk of perineum rupture (b = 1.13; 95%CI = 0.97 to 3.24; p = 0.291). Maternal employment status did not show its effect on physical activity level.Conclusion: Maternal age Ã¢â°Â¥ 35 years old increased the risk of perineum rupture. Sufficient physical activity and multiparity decreased the risk of perineum rupture. Special care should be taken on these two risk factors when assisting birth delivery in order to prevent perineum rupture.Key words: age, parity, physical activity, birth weight, perineum rupture.Correspondence: Tri Ari Hastuti. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: Triari1987@gmail.comJournal of Maternal and Child Health (2016), 1(2): 93-100https://doi.org/10.26911/thejmch.2016.01.02.04ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ  ÃÂ ÃÂ